Modulation of the NO-cGMP pathway has no effect on olfactory responses in the Drosophila antenna - Prelic, Sinisa; Getahun, Merid N.; Kaltofen, Sabine; Hansson, Bill S.; Wicher, Dieter (Frontiers in Cellular Neuroscience, 2023)
Olfaction is a crucial sensory modality in insects and is underpinned by odor-sensitive sensory neurons expressing odorant receptors that function in the dendrites as odorant-gated ion channels. Along with expression, trafficking and receptor complexing, the regulation of odorant receptor function is paramount to ensure the extraordinary sensory abilities of insects. However, the full extent of regulation of sensory neuron activity remains to be elucidated. For instance, our understanding of the intracellular effectors that mediate signaling pathways within antennal cells is incomplete within the context of olfaction in vivo. Here, with the use of optical and electrophysiological techniques in live antennal tissue, we investigate whether nitric oxide signaling occurs in the sensory periphery of Drosophila. To answer this, we first query antennal transcriptomic datasets to demonstrate the presence of nitric oxide signaling machinery in antennal tissue. Next, by applying various modulators of the NO-cGMP pathway in open antennal preparations, we show that olfactory responses are unaffected by a wide panel of NO-cGMP pathway inhibitors and activators over short and long timescales. We further examine the action of cAMP and cGMP, cyclic nucleotides previously linked to olfactory processes as intracellular potentiators of receptor functioning, and find that both long-term and short-term applications or microinjections of cGMP have no effect on olfactory responses in vivo as measured by calcium imaging and single sensillum recording. The absence of effect of cGMP is shown in contrast to cAMP, which elicits increased responses when perfused shortly prior to olfactory responses in OSNs. Taken together, the apparent absence of nitric oxide signaling in olfactory neurons indicates that this gaseous messenger may play no role as a regulator of olfactory transduction in insects, though may play other physiological roles at the sensory periphery of the antenna.